PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MODEL PEMBELAJARAN MATCH TO MATCH PADA ANAK TUNAGRAHITA RINGAN DI SDN INKLUSI - MUAYADAH, (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   One of the causes of low Indonesian learning result to mild mentally retardation children was the low of beginning readingability which appeared in reading syllables, words, and simple sentences. To solve this problem, this research used match to match model. The purpose was to enhance beginning reading ability through learning model of match to match to mild mentally retardation in SDN inclusion Wedoro Waru Sidoarjo. This research applied qualitative approach and class treatment which was implemented in 2 cycles. The data collection was done by observation and test techniques. The data analysis used flow technique including data reduction, data display, and verification. The result of beginning reading research indicated significant enhancement. The score of assessment result was showed base on the cycles. The enhancement of reading activity process by matching picture to picture, picture to writing, writing to writing increased averagely to cycle I: 30%, cycle 2: 40%. The enhancement of reading ability of mentally retardation appeared in pronouncing reading, fluent, articulateness of reading syllables, words and sentences enhanced averagely to cycle I: 32% cycle 2: 40%. The words and sentences comprehension enhanced, cycle I: 10% cycle 2: 20%. Based on the research result it could be recommended that learning model of match to match could be used as one of the strategies to enhance beginning reading of mild mentally retardation children. Keywords: beginning reading, match to match model